Free Vibration Analysis of Isotropic Plates by Alternative Hierarchical Finite Element Method Based on Reddy’s C1 HSDT - Serdoun, Nadjib Sidi Mohammed; Hamza-Cherif, S. M. (American Scientific Research Journal for Engineering, Technology, and Sciences, 2014)
This paper presents the free vibration analysis of isotropic thick rectangular plates, based on higher order shear deformation theory (HSDT). The plate theory ensures a zero shear-stress condition at the top and bottom surfaces of the plate, and do not requires a shear correction factor. The model requires inter-element C1 continuity for the transverse displacement. To overcome this hindrance, a new hierarchical p-element with six degrees of freedom per node is developed and used to find natural frequencies of thick plates. Convergence studies and comparison have been carried out for with different boundaries conditions. It is shown that the present element enables rapid convergence.